APAKAH ADA KORELASI ANTARA ASET BIOLOGIS DAN AUDITOR SWITCH TERHADAP AUDIT FEE DIMASA PANDEMI COVID-19? - Abdullah, Sulthan Yusuf; Apandi, R. Nelly Nur; Widarsono, Agus (APSSAI, 2022)
The study aims to test and analyze whether biological assets and auditor switches are correlated with audit fees during the Covid-19 pandemic with a sample of agricultural companies listed on the Indonesia Stock Exchange (IDX). The data collected were analyzed descriptively and quantitatively, followed by correlation analysis. The study results show no single variable correlated with the audit fee. This study only uses two explanatory variables to explain audit fees. For this reason, further studies can add other variables to obtain generalizable results. This research implies that it is expected to be a reference for further investigation.